Stunting Toddler Eating Patterns in The Pota Health Center Care Working Area East Manggarai District - Prima Cardayo, Kamelia; Prasetyo, Budi; Setia Ningtyas, Woro (Sekolah Tinggi Agama Islam Kuningan, 2024)
Inappropriate feeding practices could be a major cause of stunting. Stunting was one of the problems in the growth process because it was associated with an increased risk of morbidity, mortality, and suboptimal brain development. Based on data obtained from the electronic data collection of community-based nutrition recording and reporting in East Manggarai district at August weighing in 2023 from 24,427 toddlers there were 2195 stunted toddlers or 9. 0%. Pota health center was one of the health centers in East Manggarai Regency with a high number of stunted toddlers, namely 107 children or 10. 9%. The purpose of this study was to determine, describe and analyze the feeding patterns of stunted toddlers at Pota health center, East Manggarai regency. Methods: this study used a qualitative method with phenomenological research approaches. The informants in this study consisted of 7 main informants, namely mothers who had stunted toddlers in the pota puskesmas working area who were taken by purposive sampling technique. Results: mothers' perceptions of stunting tended to be the physical signs of children without knowing the long-term effects. The pattern of exclusive breastfeeding was still not good where most children were not given exclusive breastfeeding and the pattern of complementary feeding was still inadequate from the age of administration, frequency, amount, texture, variety and not knowing the complementary feeding of breast milk. Conclusion: mothers' perceptions of stunting were only related to the physical signs of the child and most informants did not gave their children exclusive breastfeeding and the pattern of complementary feeding was still inadequate from the age of administration, frequency, quantity, texture, variety and did not knew complementary feeding of breast milk.